The Effects of Repeat Testing, Malingering, and Traumatic Brain Injury on Computerized Measures of Visuospatial Memory Span - Woods, David L.; Wyma, John M.; Herron, Timothy J.; Yund, E. W. (Frontiers in Human Neuroscience, 2016)
Spatial span tests (SSTs) such as the Corsi Block Test (CBT) and the SST of the Wechsler Memory Scale are widely used to assess deficits in spatial working memory. We conducted three experiments to evaluate the test–retest reliability and clinical sensitivity of a new computerized spatial span test (C-SST) that incorporates psychophysical methods to improve the precision of spatial span measurement. In Experiment 1, we analyzed C-SST test–retest reliability in 49 participants who underwent three test sessions at weekly intervals. Intraclass correlation coefficients (ICC) were higher for a psychophysically derived mean span (MnS) metric (0.83) than for the maximal span and total correct metrics used in traditional spatial-span tests. Response times (ReTs) also showed high ICCs (0.93) that correlated negatively with MnS scores and correlated positively with response-time latencies from other tests of processing speed. Learning effects were insignificant. Experiment 2 examined the performance of Experiment 1 participants when instructed to feign symptoms of traumatic brain injury (TBI): 57% showed abnormal MnS z-scores. A MnS z-score cutoff of 3.0 correctly classified 36% of simulated malingerers and 91% of the subgroup of 11 control participants with abnormal spans. Malingerers also made more substitution errors than control participants with abnormal spans (sensitivity = 43%, specificity = 91%). In addition, malingerers showed no evidence of ReT slowing, in contrast to significant abnormalities seen on other malingered tests of processing speed. As a result, differences between ReT z-scores and z-scores on other processing speed tests showed very high sensitivity and specificity in distinguishing malingering and control participants with either normal or abnormal spans. Experiment 3 examined C-SST performance in a group of patients with predominantly mild TBI: neither MnS nor ReT z-scores showed significant group-level abnormalities. The C-SST improves the reliability and sensitivity of spatial span testing, can accurately detect malingering, and shows that visuospatial working memory is largely preserved in patients with predominantly mild TBI.